Hyers-Ulam Stability and Existence of Solutions for Nigmatullin’s Fractional Diffusion Equation - Zhuoyan Gao; JinRong Wang (Advances in Mathematical Physics)
We discuss stability of time-fractional order heat conduction equations and prove the Hyers-Ulam and generalized Hyers-Ulam-Rassias stability of time-fractional order heat conduction equations via fractional Green function involving Wright function. In addition, an interesting existence result for solution is given.